2018
DOI: 10.1111/bjso.12246
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in social control: Who ‘speaks up’ when witnessing uncivil, discriminatory, and immoral behaviours?

Abstract: This research examined the personality characteristics of individuals who 'speak up' and confront perpetrators of norm transgressions. We tested whether those who intervene tend to be 'bitter complainers' or 'well-adjusted leaders'. In four studies (total N = 1,003), we measured several individual differences that are directly implicated by at least one of the two concepts. We also presented participants with uncivil, discriminatory, and immoral behaviours and asked them how likely they would be to intervene i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 76 publications
3
23
0
Order By: Relevance
“…This generalizability replicates recent work by Moisuc, Brauer, Fonseca, Chaurand, and Greitemeyer (2018) who also found that individuals tend to react in similar ways to different types of deviant behaviors. This generalizability replicates recent work by Moisuc, Brauer, Fonseca, Chaurand, and Greitemeyer (2018) who also found that individuals tend to react in similar ways to different types of deviant behaviors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This generalizability replicates recent work by Moisuc, Brauer, Fonseca, Chaurand, and Greitemeyer (2018) who also found that individuals tend to react in similar ways to different types of deviant behaviors. This generalizability replicates recent work by Moisuc, Brauer, Fonseca, Chaurand, and Greitemeyer (2018) who also found that individuals tend to react in similar ways to different types of deviant behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…The relationship closeness effect generalized across all three types of behaviors, i.e., minor norm transgressions ("uncivil behaviors"), major norm transgressions and criminal acts ("immoral behaviors"), and hostile behaviors toward ethnic minorities ("discriminatory behaviors"). This generalizability replicates recent work by Moisuc, Brauer, Fonseca, Chaurand, and Greitemeyer (2018) who also found that individuals tend to react in similar ways to different types of deviant behaviors. Finally, our exploratory analyses showed that the relationship closeness effect increases with age.…”
Section: Discussionsupporting
confidence: 90%
“…Some opinion poll data show a tendency among older people to hold more punitive sentiments toward six common crimes (McCorkle, 1993). Across multiple norm-violation scenarios and a large sample covering the full age range, Moisuc et al (in press; Sample 3) found a reliable positive correlation between age and the self-reported tendency to confront perpetrators. Another scenario-based study found that older computer users were less permissive toward illegitimate use of a computer than younger ones (Gattiker & Kelley, 1999).…”
Section: Research Questions and Hypothesesmentioning
confidence: 92%
“…Successful bystander intervention requires taking risks and is associated with a sense of high self-efficacy, high empathy for victims, moral engagement, and high social status (Thornberg and Jungert 2013). Even among adults, the ability to intervene is correlated with altruism, extraversion, peer acceptance, emotion regulation, and autonomous sense of self (Moisuc et al 2018).…”
Section: Operant Conditioning and Information Disseminationmentioning
confidence: 99%